Sacha Inchi Energy Bars: Formulation optimization with Statistical Mix Design - Verduga, Katherine; Santamaría, Jorge Luis; Gordillo, Gilda; Montero, Carolina (Enfoque UTE, 2022)
In this work, the optimization results are presented in the formulation of an energy bar of sacha inchi (Plukenetia volubilis), applying the statistical design of mixtures for the analysis of composition and caloric power in the bar. Energy bars consisting of amaranth, quinoa, dehydrated pineapple, oats, honey and sacha inchi were developed. In each composition, the amounts of honey and sacha inchi were modified, selecting three bars with the greatest difference between their compositions and caloric power. When conducting an acceptability analysis based on the application of a survey, the potential consumers turned out to be people between 19 and 24 years old. In addition to performing an evaluation of the caloric intake to all the bars produced, a compositional or proximal analysis was carried out on the bar with the greatest acceptance, on the basis of which new formulations were developed, maintaining the caloric intake value and validating the acceptance by the consumer in each new formulation. Concluding that there are significant differences regarding the acceptance of the optimized and non-optimized bar, since the non-optimized bar has a higher content of sacha inchi than the non-optimized one (35 % wt and 30 % wt, respectively) and in terms of honey content, the non-optimized bar has a higher content than the optimized one (30 % wt and 20 % wt, respectively). An alternative energy bar was obtained that promotes the consumption of native cereals and lipids that also have a great nutritional contribution.